2021
DOI: 10.1186/s40634-021-00435-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the rate of delayed/nonunion in fifth metatarsal fractures receiving anti-inflammatory medications

Abstract: Purpose Controversy exists regarding the acute effect of non-steroidal anti-inflammatory drugs (NSAIDs) on early fracture healing. The purpose of this study was to analyze the rate of nonunion or delayed union in patients with fifth metatarsal (5th MT) fractures. We hypothesize that the use of NSAIDs would increase the rate of nonunion/delayed union in 5th MT fractures. Methods Using PearlDiver, a national insurance database was analyzed. ICD codes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
2
0
1
Order By: Relevance
“…В масштабном исследовании B. Barnds и соавт. [32] было проведено сравнение частоты задержки консолидации или несращения при переломе пятой плюсневой кости -одной из наиболее частых травм стопы, возникающей при физических тренировках и нагрузках. Среди 10 991 лица, перенесшего этот перелом за период с 2007 по 2018 г., 13,3% вынуждены были принимать НПВП как минимум в течение 2 месяцев.…”
Section: нпвп и репарация переломов: реальная клиническая практикаunclassified
“…В масштабном исследовании B. Barnds и соавт. [32] было проведено сравнение частоты задержки консолидации или несращения при переломе пятой плюсневой кости -одной из наиболее частых травм стопы, возникающей при физических тренировках и нагрузках. Среди 10 991 лица, перенесшего этот перелом за период с 2007 по 2018 г., 13,3% вынуждены были принимать НПВП как минимум в течение 2 месяцев.…”
Section: нпвп и репарация переломов: реальная клиническая практикаunclassified
“…13 In line with the findings, subjects receiving NSAIDs within 60 days of the first diagnosis in patients, Bandon et al found a statistically significant greater nonunion / delayed union of 5 th MT fractures. 18 Azmi/ JOINTS (Journal Orthopaedi and Traumatology Surabaya) October 2022; 11(2): 70-77…”
Section: Association Between Nsaids/cox-2 Inhibitors and Nonunion Fra...mentioning
confidence: 99%
“…In patients initially treated conservatively, it was shown that NSAIDs have a negative effect on the healing of the fifth metatarsal fracture. Therefore, NSAIDs are a negative prognostic factor for recovery when treated non-surgically (19).…”
Section: Image 1 Radiographs Of the Right Foot With Fracture Of The F...mentioning
confidence: 99%